Representasi Nilai Budaya Suku Batak Pada Film Ngeri- Ngeri Sedap Karya Bene Dionysius Rajagukguk - Muhammad Rafli Dwi Nur Alam Alam; Anwari (Menara Tebuireng, 2023)
Film is a means of mass communication that is in demand by many people, besides that, film is able to provide information that is easily accepted by all walks of life. This study aims to determine the Representation of the Cultural Values of the Batak Tribe in the film Ngeri-Ngeri Sedap by Bene Dionysius Rajagukguk. As for this study, the researcher formulates the problem in this thesis into two, namely: (1) What are the iconic signs, indexes and redaction symbols in Bene Dionysius Rajagukguk's Ngeri-Ngeri Sedap film. (2) How is the representation of the cultural values of the Batak tribe in the film Ngeri-Ngeri Sedap by Bene Dionysius Rajagukguk. To answer the two formulations of the problem, the researcher conducted a study using Charles Sanders Pierce's Semiotics theory. This research is a non-stakeholder qualitative research. The form of analysis used is Charles Sanders Pierce's Semiotic theory using three types of signs, namely icons, indexes and symbols. The data for this study were collected through an analysis of each scene or scene in the Ngeri-Ngeri Sedap film. The results of this study indicate that the representation of the cultural values of the Batak people in the film Ngeri-Ngeri Sedap is shown through everyday scenes carried out by the characters Pak Domu, Mak Domu, Domu, Sarma, Gabe and Sahat. Symbols of cultural values of the Batak tribe are manifested through the use of language, clothing and customs. the meaning of the cultural symbol depicted in the film Ngeri-Ngeri Sedap is the culture of the Batak tribe which is very thick with its cultural values that have been passed down from generation to generation, so that it is able to become a guideline in carrying out social life. Keyword: Representation, Cultural Values, Batak Tribe, Semiotic Analysis, Ngeri-Ngeri Sedap Films.